Driver anger in France: The relationships between sex, gender roles, trait and state driving anger and appraisals made while driving. (January 2018) - Albentosa, Julie; Stephens, Amanda N.; Sullman, Mark J.M.
Highlights: The 33-item 6 factor driving anger scale was confirmed in a sample of drivers from France. Relationships between trait anger, sex roles, sex, appraisal tendencies and anger while driving where explored. Females and those reporting more masculine traits tended to have higher levels of trait driving anger. More negative appraisals of the traffic situation were related to higher levels of state anger. Abstract: This study aimed to further understand the relationships between sex, gender identity, trait and state driving anger and situational appraisals made while driving, and to validate the 33-item Driving Anger Scale (DAS) in a sample of drivers from France. In total, 378 drivers (males = 38%) aged from 18 to 79 years completed a survey containing the 33-item DAS, the Bem Sex-Role Inventory (BSRI) and eight questions regarding self-reported state anger and appraisals in relation to a recalled recent anger provoking situation experienced while driving. Confirmatory Factor Analysis supported the original six-factor structure of the 33-item DAS. Moreover, Structural Equation Modelling of the factors associated with the recalled anger event showed that trait anger influenced state anger through negative appraisal tendencies, and this was influenced by both sex and gender roles. Females and those reporting more masculine traits tended to have higher levels of trait driving anger. Conversely, drivers with feminine traits had low state anger except if they negatively appraised the situation. This new model could be taken into consideration for developing interventions to reduce anger and "road rage" incidents.